The aftermath of 'Beirutshima': the role of nursing quantum leadership in primary health care centers - Yared, Georges J.; Tarrieh, Rima Abou; El Hajjar, Charlotte A.; Al Hasssan, Jihad M.; Abou Hammin, Saad A.; Ghazal, Kariman S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The healthcare system in Lebanon faced unprecedented challenges following the COVID-19 pandemic and the devastating beirut blast on August 4th, 2020. The aftermath highlighted the system's vulnerability, corruption, and incapacity to provide essential services, leading to an urgent need for leadership transformation within primary healthcare centers (PHCs). Methods: This qualitative cross-sectional study assessed the quantum leadership skills of nurses in 30 PHCs within a 5-kilometer radius of the blast site. Data were collected six months post-blast using a self-administered questionnaire based on a binary outcome scale of agreement and disagreement, analyzed with IBM SPSS-19 software to evaluate the potential for leadership improvement. Results: The findings indicate a significant correlation between quantum leadership skills and the operational effectiveness of PHCs, particularly those managed by the Ministry of Public Health, which exhibited superior quantum leadership skills compared to others. Conclusions: The study underscores the necessity for a new leadership paradigm rooted in quantum theory to navigate the healthcare system through crises effectively. A quantum leader, characterized by heightened organizational consciousness and energy, is pivotal for ensuring a seamless transition towards recovery and resilience, ultimately fostering a breakthrough in the face of systemic breakdowns.